Motion Picture Paradise : A History of Florida's Film and Television Industry. - Morton, David (University Press of Florida, 2024)
This book is a sweeping story of filmmaking in Florida, chronicling the state's importance to producers throughout 125 years by looking at the many iconic films and television shows made across the peninsula.